Significant concordance of genetic variation that increases both the risk for obsessive–compulsive disorder and the volumes of the nucleus accumbens and putamen - Hibar, Derrek P. (Br J Psychiatry, 2018)
BACKGROUND: Many studies have identified changes in the brain associated with obsessive–compulsive disorder (OCD), but few have examined the relationship between genetic determinants of OCD and brain variation. AIMS: We present the first genome-wide investigation of overlapping genetic risk for OCD and genetic influences on subcortical brain structures. METHOD: Using single nucleotide polymorphism effect concordance analysis, we measured genetic overlap between the first genome-wide association study (GWAS) of OCD (1465 participants with OCD, 5557 controls) and recent GWASs of eight subcortical brain volumes (13 171 participants). RESULTS: We found evidence of significant positive concordance between OCD risk variants and variants associated with greater nucleus accumbens and putamen volumes. When conditioning OCD risk variants on brain volume, variants influencing putamen, amyg-dala and thalamus volumes were associated with risk for OCD. CONCLUSIONS: These results are consistent with current OCD neurocircuitry models. Further evidence will clarify the relationship between putamen volume and OCD risk, and the roles of the detected variants in this disorder. DECLARATION OF INTEREST: The authors have declared that no competing interests exist.